2021
DOI: 10.3390/agronomy11122572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Rates on the Productivity and Nutritive Value of Forage Grass Grown under Extreme Climatic Conditions

Abstract: This vegetative experiment was carried out at the greenhouse of Vytautas Magnus University Agriculture Academy Open Access Joint Research Centre of Agriculture and Forestry (Lithuania) in 2020–2021. The aim of these studies was to determine the effect of different nitrogen rates on the productivity and nutritional quality of forage grasses (a mixture of red clover and timothy) under the most common extremes of climate change, i.e., soil moisture deficiency and surplus. Under drought and waterlogging stresses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…This study revealed a significant reduction in the biomass of red clover under drought stress, while no such effect was observed in the grass. This aligns with a previous study, which also showed that clover exhibited higher sensitivity to drought stress when compared to timothy [44]. A significant difference between the aboveground biomasses of mixed culture and monoculture stands during both drought and recovery phases was observed (Figure 2A-D).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed a significant reduction in the biomass of red clover under drought stress, while no such effect was observed in the grass. This aligns with a previous study, which also showed that clover exhibited higher sensitivity to drought stress when compared to timothy [44]. A significant difference between the aboveground biomasses of mixed culture and monoculture stands during both drought and recovery phases was observed (Figure 2A-D).…”
Section: Discussionsupporting
confidence: 92%